PROGRAMS OF TECHNOLOGY ENTREPRENEURS - Inche Mitma, Jorge Luis (1998)
E1 entrepreneur program at the Faculty of Industrial Engineering, is a proposal for an alternative development for students and graduates with training in Industrial Engineering. Not only because of the current situation in the country which is manifested in high levels of unemployment and underemployment, but because of the importance of entrepreneurship in society and the benefits of business training for those with entrepreneurial initiatives in the country valued.